Comparative Fibrinolytic Properties of Staphylokinase and Streptokinase in Animal Models of Venous Thrombosis - Lijnen, H R; Stassen, J M; Vanlinthout, I; Fukao, H; Okada, K; Matsuo, O; Collen, D (Thrombosis and Haemostasis, 1991)
The thrombolytic and pharmacokinetic properties of staphylokinase were compared with those of streptokinase in hamsters with a pulmonary embolus produced from human plasma or from hamster plasma, and in rabbits with a jugular vein blood clot produced from rabbit blood. In both models, a continuous intravenous infusion of staphylokinase and streptokinase over 60 min in hamsters or over 4 h in rabbits, induced dose-dependent progressive clot lysis in the absence of significant systemic activation of the fibrinolytic system. The results of thrombolytic potency (clot lysis at 30 min after the end of the infusion, in percent, versus dose administered, in mg/kg) were fitted with an exponentially transformed sigmoidal function and the maximal percent clot lysis (c), the maximal rate of lysis (z = ¼ac · eb) and the dose at which the maximal rate of lysis is achieved (b) were determined. In hamsters with a pulmonary embolus produced from human plasma, streptokinase had a somewhat higher thrombolytic potency than staphylokinase, as revealed by a higher z value (2,100 ± 1,100% lysis per mg/kg streptokinase administered versus 1,100 ± 330% lysis per mg/kg for staphylokinase). In hamsters with a pulmonary embolus produced from hamster plasma, staphylokinase had a somewhat higher thrombolytic potency than streptokinase (z = 1,600 ± 440 versus 1,200 ± 370% lysis per mg/kg). Staphylokinase had a higher thrombolytic potency than streptokinase in rabbits, as revealed by a higher z-value (950 ± 350% lysis per mg/kg staphylokinase administered versus 330 ± 39% lysis per mg/kg for streptokinase) and a lower b-value (0.035 ± 0.010 mg/kg staphylokinase versus 0.091 ± 0.008 mg/kg for streptokinase). The plasma clearance following bolus injection of staphylokinase or streptokinase in hamsters or rabbits was comparably rapid (1.1 to 1.4 ml/min in hamsters and 14 to 15 ml/min in rabbits) as a result of a short initial half-life (1.8 to 1.9 min in hamsters and 1.7 to 2.0 min in rabbits). These results in two quantitative rodent models of thrombolysis suggest that staphylokinase is a potent thrombolytic agent with an in vivo thrombolytic potency that is comparable to that of streptokinase. Further investigation of the thrombolytic potential of staphylokinase seems to be warranted.